Про хід, результати та проблеми оцінювання наукових установ Національної академії наук України у 2023 році - Єгоров, І.Ю.; Жукович, І.А.; Красноносова, О.М.; Артюшенко, В.В. (Вісник НАН України, 2024)
У статті висвітлено результати оцінювання ефективності діяльності наукових установ НАН України та їхніх підрозділів, яке відбувалося у 2023 р. за оновленою Методикою оцінювання НАН України, а також результати апробації бальної системи оцінювання, що проводилася одночасно. Розкрито деякі організаційні аспекти процесу оцінювання. Розглянуто результати опитування експертів та членів постійних комісій за науковими напрямами секцій НАН України щодо запровадження бальної системи оцінювання на постійній основі. Проаналізовано особливості оцінювання у 2023 р. і проблеми, що виникали під час його проведення. Organizational aspects of evaluating the effectiveness of the scientific activities of the NASU institutions and their divisions are presented in the article. The purpose of the article consists in the analysis of the evaluation results which presented the effectiveness of the scientific activities of the institutions and their divisions, with the evaluation process taking place in 2023 according to the new Evaluation Methodology, and the results of the testing of the evaluation in points, which was carried out at the same time. The tasks of this work also include results analysis for a survey of the experts’ opinions and those of members of the Standing Commissions for the NASU scientific directions of the NASU sections on the permanent conduct of evaluation in points. In addition, the features of the evaluation in 2023 and the problems of its implementation and testing of the scoring system are determined. It is difficult to fully formalize the evaluation process, because a lot of activities and their results can’t be presented in quantitative form. While the criteria and indicators for evaluation, as well as the methods of their determination, can be the subject of debate, the need for a faster solution to two organizational problems is not disputable. The first of them is the problem of forming a pool of experts with the involvement of foreign specialists. Formation of a pool of experts should ensure greater objectivity of generalized assessments. The second problem is the creation of universal information systems (in the form of userfriendly data arrays placed on the web) for conducting not only a “spot” evaluation every five years, but also for the introduction of monitoring by the Academy’s governing bodies and providing information for state certification by the Ministry of Education and Science of Ukraine. This will make it possible to reduce the time for the preparation of evaluation materials, provided that the specifics of both procedures is preserved: while for the Ministry of Education and Science of Ukraine it is necessary to obtain a quantitative assessment of the institution as a whole, and then to compare it with the results of attestation in other agencies, for the Academy it is no less important to identify weak units and develop the ways to improve efficiency and propose measures for possible reorganization.